Effect of Tithonia Diversifolia (Hemsley) A.Gray and Curcuma Domestica Val Extracts Combination Against Nodule and Body Weight In Cancer Rats Model - Mae Sri Hartati Wahyuningsih; Wahyu Nur Halimah; Woro Rukmi Prtiwi (Majalah Farmaseutik, 2017)
Kembang bulan [Tithonia diversifolia (Hemsley) A. Gray] is a potentially anticancer plants  that have been previously shown have cytotoxics effect on WiDr colon cancer cells, IC50=61.55µg/mL. Turmeric (Curcuma domestica Val.) is widely used in traditional medicine. Curcuminoids compounds from turmeric have potential anticancer activity with possibly modulate immune function mediated by lymphocytes. With the immunostimulant effect of turmeric when mixed with kembang bulan as an anticancer candidate is expected to synergize better. This study aims to determine the potential of T. diversifolia and C. domestica ethanolic extracts combination in cancer rats model by measuring weight, number of nodules, and nodule volume animals. The study was a quasi-experimental study. Mixed 70% ethanol extract of kembang bulan’s leaves and turmeric’s rhizome divided into 3 doses, 40:150mg, 80:150mg, and 160:150mg. Then it given to each group of rats by orally that had experienced breast cancer . After that, see potential on body weight, number of nodules, and nodule volume. Then compared with normal group, negative control group, and positive control group. Furthermore, the percentage change in each treatment group were compared and statistically tested using ANOVA analysis. Comparison of the results of rat’s body weight between the control group (doxorubicin) and test group showed significantly no different results. Comparison of the results of rat’s breast cancer nodule volume between the control group and the test group showed significantly no different results. A combination of 70% ethanol extract of kembang bulan’s leaves and turmeric’s rhizome have no significant effect on body weight and breast cancer nodules.